2006
DOI: 10.1074/jbc.m507871200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Loss of Fine Tuning of Gq/11 Signaling by RGS2 Protein Exacerbates Cardiomyocyte Hypertrophy

Abstract: Alterations in cardiac G protein-mediated signaling, most prominently G q/11 signaling, are centrally involved in hypertrophy and heart failure development. Several RGS proteins that can act as negative regulators of G protein signaling are expressed in the heart, but their functional roles are still poorly understood. RGS expression changes have been described in hypertrophic and failing hearts. In this study, we report a marked decrease in RGS2 (but not other major cardiac RGS proteins (RGS3-RGS5)) that occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 55 publications
5
81
0
Order By: Relevance
“…RGS2-mediated protection against myocyte hypertrophy has been previously reported in neonatal myocytes using RGS2 RNAi (18). Here, we examined adult myocytes from Rgs2 +/+ and Rgs2 -/-mouse hearts and found enhanced protein synthesis in cells incubated with the G q agonist endothelin-1 (ET1).…”
Section: Rgs2 Is Expressed In Adult Mouse Myocytes and Suppresses G Qmentioning
confidence: 99%
See 1 more Smart Citation
“…RGS2-mediated protection against myocyte hypertrophy has been previously reported in neonatal myocytes using RGS2 RNAi (18). Here, we examined adult myocytes from Rgs2 +/+ and Rgs2 -/-mouse hearts and found enhanced protein synthesis in cells incubated with the G q agonist endothelin-1 (ET1).…”
Section: Rgs2 Is Expressed In Adult Mouse Myocytes and Suppresses G Qmentioning
confidence: 99%
“…Mice globally lacking RGS2 were found to develop modest systemic hypertension, although they exhibit no major cardiac phenotype (17), which suggested that RGS2 had a modest role in the heart. Yet more recent studies found that knockdown of the gene encoding RGS2 amplifies hypertrophic responses in neonatal myocytes exposed to G q stimuli (18).…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal rat cardiomyocytes were isolated from 2-day-old SpragueDawley rats by enzymatic digestion 19 and separated from nonmuscle cells on a discontinuous Percoll gradient as described previously. 19 Detailed methodology is included in the online supplementary data.…”
Section: Neonatal Rat Cardiomyocyte Isolation and Culturementioning
confidence: 99%
“…Recognition of the deleterious effects of overactivation of the renin-angiotensin system (RAS) and AT1-Gq/G13 signaling [28][29][30], in addition to desensitization of cardioprotective βAR-Gs signaling [31][32][33], has made RAS a major therapeutic target, whether systemically or regionally [34,35]. In many randomized, controlled trials, ACE inhibitor (ACEi) reduced morbidity and mortality more than comparators in patients with congestive heart failure and coronary heart disease [36][37][38][39][40].…”
Section: Heart Failure and At1 Signalingmentioning
confidence: 99%